CYBER COMPONENTS OF COLORED REVOLUTIONS: THE EUROMAIDAN CASE - Stojanović, Lazar (Political Review, 2023)
Cyberspace represents an increasingly important ground for the realization of the most diverse ideas and goals. In addition to the undeniable facilitation of everyday activities, cyberspace is also becoming the subject of abuse in the most diverse spheres of society. The presence of a large number of actors, along with the simplicity and efficiency of the execution methods, opens up wide possibilities. The field of political action is by no means left out, what is more, it represents an important sphere of interest on which it is possible to exert influence by imposing political ideas. The genesis of such a process often leads to significant socio-political changes. The paper, starting from more general insights, points to the main characteristics of both cyberspace and color revolutions. It represents the historical component of both syntagms, successively bringing them closer to a concrete example, which is presented in detail in the central part of the paper. In this sense, the primary goal of the work is to approach the causal relationship between cyberspace and color revolutions with a special reference to the political change in Ukraine better known as the Euromaidan revolution. For this purpose, a combination of basic research methods, analytical and synthetic, will be applied. Through the gradual analysis of key concepts, the subject of research is first broken down into factors that are analyzed individually, while later they are synthesized by systematic procedures, creating a meaningful whole.